PENGARUH KOMPOSISI DEWAN KOMISARIS, KARAKTERISTIK KOMITE AUDIT, DAN MANAJEMEN LABA TERHADAP FEE AUDIT - Sukaniasih, Ni Kadek; Tenaya, Agus Indra (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The purpose of this research is to find empirical evidence of the independence of the board of commissioners, board size, the independence of the audit committee, the audit committee size, intensity of the audit committee meetings, and management fee income to audit the companies listed in the Indonesia Stock Exchange. Purposive sampling method as the sampling methods of research, in order to obtain the amount of sample in one (1) year as many as 28 companies. Analysis of the data used is multiple linear regression with t test equipment. The results of this study indicate the size of the board of directors, audit committee size, intensity of the audit committee meetings, and the size of the company has a significant influence on the audit fee. While variable commissioners independence, the independence of the audit committee, and management fee income is not significant to the audit fees.
Keywords: board of commissioners; audit committee; earnings management; audit fee